PROBLEMS OF INFLUENCE OF THE GROUND ENVIRONMENT ARE ON CORROSION OF MAIN GAS PIPELINES OF UKRAINE - KORNIIENKO, S.; KORBUTIAK, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The state of linear part of the gas-transport system of Ukraine is analyzed. The process of corrosion of main gas pipelines is considered in the ground conditions. It is set that for gas industry a problem of corrosion protection of gas pipelines is very actual, as linear part of the gas pipeline system of Ukraine is most obsolete in Europe and that one of main reasons of emergency situations there is the ground corrosion. The use of complex method of researches, analytical decisions and experimental study, is recommended in the field and laboratory conditions, creation of multivariable model of the ground environment, modeling with computer hardware and software support.